Return Difference Analysis of Two- input Planetary Gear Reducer - Zhang Yunbo; Cao Bing; Zhang Xiaofei (Jixie chuandong)
A certain type of two- input planetary gear of spacecraft steering gear system is described. By considering the influence of tooth thickness deviation,central distance deviation and bearing radial clearance on the backlash,the quantitative analysis of the two- input planetary gear return difference is carried out,the calculation expression of its return difference is given. According to the return difference analysis,by using the method with matching center distance to control return difference precision of prototype,through the test of prototype return difference,the experimental results are consistent with expectation.